Gambaran Kualitas Hidup Pada Aspek Hubungan Sosial Penderita Hipertensi Di Wilayah Puskesmas Pajang Surakarta - Mila Setyowati Putri; Supratman Supratman (Universitas Muhammadiyah Surakarta, 2021)
Background: hypertension is an illness that is chronic but it often does not prescribe characteristic symptom. Health pertaining to life style often is one factor for someone hypertension disease. The 140 mmHg in systolic and the diastolic fixed or lower than the 90 mmHg. The aspect of the quality of life of social relationships that not capable of interact, good to the family, friend, couple, the son of even the surrounding community will increase the risk of hypertension. In general would hold up progress on a decrease in the quality of life of. Research objectives: research aims to understand the quality of life of social relationship in patients hypertension in the Puskesmas Pajang Surakarta. Benefits: can know whether in the region of Puskesmas Pajang Surakarta. The image of improving the quality of social relationships is good, enough or is weak. Research methodology: Descriptive quantitative research to obtain a simple life the quality of life of social relationships in sufferer hypertension in the Puskemas Pajang Surakarta. The sample is elderly disease sufferers are hypertension is the Puskesmas Pajang Surakarta and were selected based on criteria sample. A measuring instrument used for measuring the quality of social relationships using 5 WHOQOL-BREF the questionnaire who are domain 3 on the quality of social relations and other 2 studies about the quality of life of thoroughly and health have generally. The results of the study: statistical analysis obtained the results, from 48 respondents there ere 25 respondents (52,1%) having the quality of life of social relationship good, respondents who have the quality of relationships social enough of 22 respondents (45,8%) and respondents who have the quality of life of social relationships less of 1 respondents (2,1%). A conclusion: it should also be noted it is anticipated that analysis of the research done by the city government concludes that the aspect of the quality of life of the social relationship on sufferer hypertension in the region of the Puskesmas Pajang Surakarta yields here of either.